2019
DOI: 10.1111/jfpe.13215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sensory and texture profile analysis properties of stored Khalal Barhi dates nondestructively using Vis/NIR spectroscopy

Abstract: It is important to facilitate evaluating fruit quality during harvesting and postharvest operations with simple, fast, and nondestructive tests. The purpose of this study was to evaluate TPA Barhi dates texture parameters (hardiness, cohesiveness, and chewiness) at three maturity stages: Kimri (green), Khalal (green to yellow), and Rutab (brown). The Khalal stage can be further classified into three phases: 80, 90, and 100% yellow utilizing spectra analysis. The texture properties of fresh fruit were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…The upward shift of the spectra curves reflects the transition of ripening stages of fruit maturity. Similar findings were reported by Alhamdan and Atia (2016) and Alhamdan et al, (2019) on Barhi date fruit.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The upward shift of the spectra curves reflects the transition of ripening stages of fruit maturity. Similar findings were reported by Alhamdan and Atia (2016) and Alhamdan et al, (2019) on Barhi date fruit.…”
Section: Resultssupporting
confidence: 92%
“…The spectrum data were analyzed using (F-750 Data Viewer Software, Version: v1.1.0.51). To correlate reflectance (1st and 2nd derivatives) at 285–1200 nm, the Model Builder (Version: v1.1.0.105) was used as illustrated in Alhamdan and Atia, 2017 , Alhamdan et al, 2019 .…”
Section: Methodsmentioning
confidence: 99%
“…Xie et al (2018) reported that the 1-methylcyclopropene combined with commercial polyethylene bags can effectively maintain the texture properties of blueberry. Recently, texture parameters of the fruit of the Barhi date at different maturity stages were evaluated by near-infrared (NIR) spectroscopy, which is a powerful nondestructive tool that can be used to determine fruit quality attributes (Alhamdan et al, 2019;Nicolaï et al, 2006). Therefore, TPA has played an important role in evaluating the mechanical and physical characteristics of fruits, as well as raw ingredients and finished products (Sato and Yamada, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The specific wavelength of 1359 nm might be associated with the C-H bond, suggesting a shift in polysaccharide profile, which is linked to texture modification of plants, whereas wavelengths between 1000 and 1200 nm are related to C-O groups [63]. Alhamdan et al [64] identified that lower wavelength regions, at 385-935 nm, 382-920 nm, and 630-772 nm, were able to provide information on hardiness, cohesiveness, and chewiness of date fruits. Finally, the spectral region between 2000 and 2400 nm can be used to determine the presence of various pectins (i.e., soluble and proto-pectins) [65], while the absorption peaks between 1790 and 1706 nm are associated with C = O groups, illustrating the presence of different organic compounds [66].…”
Section: Near-infrared Spectramentioning
confidence: 99%